2007
DOI: 10.1080/10826080701204904
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents and Tobacco Use: Systematic Review of Qualitative Research Methodologies and Partial Synthesis of Findings

Abstract: After a brief overview of adolescent tobacco control, methodological features and content areas of 78 qualitative studies of adolescent smoking published in English prior to September 2002 were assessed. Narrative syntheses of three content areas - peer influences, access/sales issues, and dependence/addiction - were also undertaken. Many studies failed to provide sufficient sampling and subject characterization details and more effort was required to demonstrate data validity and reliability. Syntheses of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 134 publications
0
10
2
Order By: Relevance
“…Contrary to this study, Walsh and Tzelepis (2007) found that peer pressure to use substances was mentioned by a small number of students from low socio-economic status families. Walsh and Tzelepis, however, made their observations from a study done in the United Kingdom, where societal stratification is based, among other things, on social polymorphism.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Contrary to this study, Walsh and Tzelepis (2007) found that peer pressure to use substances was mentioned by a small number of students from low socio-economic status families. Walsh and Tzelepis, however, made their observations from a study done in the United Kingdom, where societal stratification is based, among other things, on social polymorphism.…”
Section: Discussioncontrasting
confidence: 49%
“…Positive reinforcement probably occurs as substance use receives undeserving glorification as a cool, stylish, and trendy activity among youth. It has been suggested, for example, that peers encourage smoking initiation (Walsh & Tzelepis, 2007) and subsequent smoking behavior (Dawson, Sotelo, Roesch, & Klonoff, 2013), despite the health and social flaws associated with use of tobacco and its products (Jiloha, 2009). The phenomenon of peer influence and social learning is possibly reflected in media commercials portraying teenagers actively promoting alcoholic and tobacco products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, campaigns encouraging teenagers to support their friends who are trying to quit smoking holds promise as one part of a maintenance program. In a recent review of qualitative research on adolescent tobacco use, Walsh and Tzelepis (2007) reported that, while teenagers thought that the emotional support of friends and family would be helpful to them in quitting smoking, few peers offer that support.…”
Section: Discussionmentioning
confidence: 99%
“…This disparity in prevalence is an opportunity for the tobacco industry to sustain itself in declining markets; its efforts to target disadvantaged groups have been documented 23 24. The need for qualitative research to understand how tobacco control impacts on disadvantaged groups has been recognised for some time,25 26 as has the need to research the social context of youth smoking 20 27 28. Qualitative research among adults shows that tobacco control policies are experienced differently by socioeconomic class and relative position 26 29.…”
Section: Introductionmentioning
confidence: 99%